WINTER SPORTS DEVELOPMENT TRENDS STUDY ON A NATIONAL AND INTERNATIONAL PLAN (GYMNASIUM, 2009)
The accelerated pace of development of major world economies, the technological progress, thebehavior and demands of a bigger and bigger mass of people, but also the worrying effects of globalwarming, generates international development trends in the area for winter sports and related industries, thatneed to be understood and undertaken by Romania in order to remain on the world map of engaging in suchactivities.The current level of global development of tourism, of industries and services in the area of winterrecreational activities is very high.At this point, Romania should show more clairvoyance and realism in promoting the winter tourismpolicies.